Krisis Covid-19 Sebagai Prediktor Kebijakan Dividen: Bukti Dari Perusahaan Sektor Industri Dasar Dan Kimia (Jurnal Proaksi, 2023)
AbstractThis study examines the impact of the COVID-19 crisis on dividend policy, specifically examining basic and chemical industry in Indonesia. The research was conducted from 2014 to 2020 using purposive sampling technique. The sample collected was 39 companies, with a total of 273 observation units. The statistical analysis instrument used is dynamic panel data regression with FD-GMM method approach. STATA version 22 was used for parameter estimation. The research result is that the COVID-19 crisis had a positive effect on dividend policy. In times of crisis, companies in the basic and chemical industry in Indonesia tend to suppress, even eliminate dividends distributed. This result contributes to the basic industrial and chemical companies to suppress dividend distribution during the crisis in order to survive. In addition, investors need to consider stock investment instruments of this sector for dividends as part of the returns during crisis optimally.Keywords:  Crisis; COVID-19; Dividend Policy; Basic Industry; Chemical Industry